Calibration system for the Tracking Accuracy Measurement System (TAMS) using differential GPS (dGPS) - Mountain, Alan Neil (Department of Electrical Engineering, 2024)
The accuracy of a combined Optronics and Radar Tracker system is investigated in this dissertation. The Tracking Accuracy Measurement (TAMS) was designed to exploit the positional accuracy of differential Global Positioning System (dGPS) technology to qualify a 60km range X-band combined Optronic and Radar Tracker System. In essence, a roving GPS receiver, capable of measuring high dynamic movement, is mounted onboard an airplane and records target position as it is tracked by the sensor. At the sensor, a similar recording station records the GPS position of the sensor, and is carefully surveyed into the co-ordinate system of the sensor. The TAMS also records the sensor output, which is carefully time-stamped with GPS time. Post mission, the raw GPS is differentially corrected. An algorithm was written in Matlab for the purpose of comparing the dGPS measurements and the sensor measurements, once suitable interpolation and correction for sensor latency has taken place. The accuracy of the sensor latencies were investigated, and it was found that the latencies for both the Optronic and Radar sensors were off by a marginal time delay. It was concluded that the direction and speed of the airplane would account for this anomaly, but a more in-depth investigation should be considered. The accuracy of the Tracker was calculated using statistical methods, and the accuracy computed for the data received for this dissertation was compared to the required Tracker specifications. Because only data from the 5km and 10km range bin was available for the analysis, the Tracker could only be quailified at these range bins. The result of the statistical analysis showed that the Tracker system meets specification at the 5km and 10km range bin.